Numbers of spermatozoa in queens and drones indicate multiple mating of queens in Apis andreniformis and Apis dorsata. - Koeniger, Gudrun; Koeniger, N.; Mardan, Makhdzir; Punchihewa, R. W. K.; Otis, G. W. (1990)
Drones of Apis dorsata had an average of 2.46·106 spermatozoa in their vesiculae seminales. Two queens had 3.67·106 spermatozoa in their spermathecae. In A adreniformis, drones had an average of 0.13·106 and the spermathecae of 2 queens contained 0.98 and 1.09·106 spermatozoa. In both A dorsata and A andreniformis the spermathecae of queens contained more spermatozoa than the vesiculae seminales of a single drone of either species. Therefore, we conclude that multiple mating occurs in both species as is the case for A mellifera, A cerana and A florea.